Self‐stigma and the intention to seek psychological help online compared to face‐to‐face. Issue 7 (8th January 2018) - Wallin, Emma; Maathz, Pernilla; Parling, Thomas; Hursti, Timo
Abstract: Objectives: The present study aims to investigate the impact of help‐seeking self‐stigma on the preference and intention to seek psychological treatment delivered online compared to face‐to‐face. Design: This study uses survey data from two Swedish samples. Sample 1 consists of 267 students (78.7% women) with a mean age of 24.5 ( SD = 6.1). Sample 2 consists of 195 primary care patients (56.9% women) with a mean age of 45.3 ( SD = 17.7). Results: The number of participants who preferred online treatment was higher if seeking psychological help for a perceived stigmatized problem compared to mental health problems in general. The odds ratios for choosing treatment online over face‐to‐face were 6.41, 95% CI [4.05, 10.14] in Sample 1 and 11.19, 95% CI [5.29, 23.67] in Sample 2. In addition, findings suggest that higher levels of help‐seeking self‐stigma predicted higher intention to seek treatment online compared to face‐to‐face. Conclusions: Our results suggest that online interventions may facilitate help‐seeking among individuals deterred by stigma.